An identification and functional evaluation of a novel CYP2C9 variant CYP2C962 - Chen, Hao; Dai, Da-Peng; Zhou, Shan; Liu, Jian; Wang, Shuang-Hu; Wu, Hua-Lan; Zhou, Quan; Geng, Pei-Wu; Chong, Jia; Lü, You; Cai, Jian-Ping; Yang, Jie-Fu (Chemico-biological interactions, 2020)
Warfarin is the most commonly used anticoagulant in the clinical treatment of thromboembolic diseases. The dose of warfarin varies significantly within populations, and the dose is closely related to the genetic polymorphisms of the CYP2C9 and VKORC1 genes. In this study, a new CYP2C9 nonsynonymous mutation (8576C > T) was detected after the genetic screening of 162 patients took warfarin. This mutation, named as the new allele CYP2C9*62, can result in an arginine to cysteine amino acid substitution at position 125 of the CYP2C9 protein (R125C). When expressed in insect cells, the protein expression of CYP2C9.62 was significantly lower than that of the wild-type, and its metabolic activity was also significantly decreased after the addition of three typical CYP2C9 probe drugs, suggesting that the new mutant can dramatically affect the metabolism of CYP2C9 drugs in vitro.